Study of Dielectric Relaxation Behavior of Liquid Crystal Copolyester Vectra-A by Thermally Stimulated Discharge Current Technique. (27th March 2013) - Kalia, Sapna; Sharma, J. K.; Sharma, Vandana
Abstract : The dielectric relaxation behavior of thermotropic liquid crystal copolyester of 73% of p-hydroxy-benzoic acid (HBA) and 27% of 2-hydroxy-6-naphthoic acid (HNA) (Vectra-A) at poling temperature 80°C has been studied using thermally stimulated depolarization current (TSDC) technique in the temperature range from 15°C to 250°C. The TSD currents were obtained for different polarizing fields ranging from 3.8 kV/cm to 19.2 kV/cm. TSD current spectra in the temperature range from 15°C to 250°C show three current maxima around 25°C, 110°C, and 220°C. The maxima around 25°C and 110°C correspond to characteristic dipolar relaxations β and α, respectively. The peak around 220°C is due to space charge effects named as δ -relaxation. The various relaxation parameters like activation energy ( U ), relaxation strength( Δ ε ), preexponential factor( τ 0 ), the quantity of charge released ( Q ) and concentration of trap( N t ) for β - and α -relaxations at polarizing temperature 80°C for different polarizing fields were evaluated using Bucci-Fieschi fit. The linear variation between activation energy and natural logarithm of preexponential factor indicates the presence of compensation effect for dipolar relaxations of Vectra-A under present poling conditions.